Managing plant pests with soaps - Matthew A. Borden; Adam G. Dale (EDIS, 2019)
Home gardeners and professionals frequently discuss the use of soap products to control plant pests. Limited and conflicting information on this topic has resulted in confusion and misuse of products. It is important to recognize that all soaps are not equal in safety or efficacy in plant-pest management. This 5-page fact sheet written by Matthew A. Borden and Adam G. Dale and published by the UF/IFAS Entomology and Nematology Department describes some of the different types of soaps and recommendations for proper, legal, and safe use of these products to manage pests. https://edis.ifas.ufl.edu/in1248